Trials and Tribulations: Problematizing the City through/as Urban Experimentation. Issue 10 (October 2016) - Evans, Joshua
Abstract: This review article addresses the phenomenon of urban experimentation. Urban experimentation has achieved notable significance in recent years. Viewing the city as a laboratory for field‐testing new practices, or as a setting for experimental sites, has earned significant cache when it comes to contemporary urban issues such as governance reform, urban sustainability and economic development. In this regard, urban experiments are an important vehicle for not only understanding the city but also transforming it. This article reviews how experimentation has been defined teasing out some basic concepts before examining how experimentation has been broadly applied across urban studies. The paper then draws attention to three realms of urban development – social, economic, and sustainability – and asks how experimentation in these realms acts as a mode of problematization that summons particular forms of governance, the implications of which are summarized.